MAKNA PERIBAHASA MADURA DAN STEREOTIP KEKERASAN PADA ETNIS MADURA (TINJAUAN STILISTIKA) - Nugraha, Anandika Panca (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2017)
This article studies the meaning of Madurese proverbs commonly associated with violence stereotype of the Madurese. The analysis is conducted by using stylistic approach while the data are collected by means of documentary method. The findings show that Madurese proverbs represent a number of meanings related to violence, that is, physical violence, robust conviction and advice on violence. Those meanings do not necessarily justify the violent nature of the Madurese. Rather, they much imply the principles of Madurese people to strongly uphold self dignity, courage and righteousness. Further research using larger data of Madurese proverbs and other types of Madurese proverbs is suggested in order to obtain comprehensive depiction about Madurese values.